Inorganic mixed thermal insulation mortar and preparation method thereof
By optimizing the assembly distribution ratio and preparation method of inorganic mixed insulation mortar, an efficient and low-cost inorganic light aggregate mixed insulation material is formed, which solves the problems of material inhomogeneity and uneven release of hot and cold stress in the floor insulation design of building buildings in the prior art, and achieves the effect of improving building insulation energy saving efficiency and engineering quality.
Patent Information
- Application Number
- CN202411963659.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-29
AI Technical Summary
The existing inorganic insulation mortar has problems such as material inhomogeneity, layering hollowing, shrinkage cracking, and hot and cold stress release in the floor insulation design of building buildings, making it difficult to take into account both thermal calculation and ground bearing mechanism problems.
An inorganic mixed insulation mortar is adopted, and its components include composite silicate cement, homemade machined sand, mineral stone powder, modified inorganic vitrified microbeads, activated magnesium oxide, dispersible latex powder, cellulose ether, homemade crystalline waterproofing agent and polypropylene fiber. By optimizing the ratio and preparation method of these components, an efficient and low-cost inorganic light aggregate mixed insulation material is formed.
The high-quality, efficient and low-cost properties of inorganic mixed insulation mortar are achieved, and the problems of material inhomogeneity and uneven release of hot and cold stress are solved, building insulation energy saving efficiency and project quality are improved, costs are reduced and ecological environment is protected.
Smart Images

Figure CN119899002A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of construction, and in particular to an inorganic mixed thermal insulation mortar and a preparation method thereof. Background Art
[0002] With the sustained growth of my country's national economy and the continuous progress of science and technology, society's requirements for the quality of indoor building environment are increasing. In winter heating buildings, the evaluation of indoor conditions has traditionally relied only on the key indicator of indoor temperature, but this is not comprehensive. The thermal performance of building maintenance structures, especially the ground, is closely related to human health. People spend most of their time indoors with their feet in contact with the ground. In order to maintain health, the human body needs to maintain thermal balance with the surrounding environment, which causes a large amount of heat loss in the feet. Too low ground temperature will not only cause the feet to feel cold and uncomfortable, but may also cause rheumatism, arthritis and other diseases. In addition, the thermal performance of the ground has a significant impact on the indoor temperature. A good building ground can not only improve the indoor thermal comfort, but also contribute to the insulation and energy saving of the building. This should be given full attention.
[0003] In the field of building energy conservation, the use of thermal insulation materials is the main way to achieve energy conservation. As a country with relatively scarce energy resources, China's research and development of new thermal insulation materials can not only bring higher economic benefits, but also have the advantages of short cycle, quick results and low investment. With the introduction of the concept of building energy conservation, the development of thermal insulation mortar has received widespread attention. Internationally, the United States, Germany and other countries have conducted in-depth research in the field of thermal insulation mortar and formulated relevant standards.
[0004] Building insulation mortar can be divided into two categories according to chemical composition: organic insulation mortar and inorganic insulation mortar. Although organic insulation mortar is widely used in areas with hot summers and cold winters and has good thermal insulation properties, it has problems such as poor construction and workability, poor environmental protection, flammability, poor weather resistance, easy aging, shrinkage and cracking. Inorganic insulation mortar, as a new type of insulation material, effectively solves the above problems with its unique performance advantages. However, at present, inorganic insulation mortar is mainly used in building interior and exterior wall insulation projects. For the energy-saving design of building floors and roofs, the optional inorganic insulation materials are relatively limited.
[0005] In the prior art, the thermal insulation design of building floors needs to take into account both thermal calculations and ground bearing mechanics. The commonly used design method is to add inorganic thermal insulation mortar and cement mortar leveling layer on the floor layer. Although this multi-layer design and layered construction method are common, due to the differences in dry surface density, strength, linear shrinkage, thermal conductivity, etc. between inorganic thermal insulation materials and cement leveling mortar, it is easy to cause material inhomogeneity, causing problems such as delamination, hollowing, shrinkage cracking, and uneven release of cold and hot stresses. Summary of the invention
[0006] In view of the above situation, the present invention provides an inorganic mixed thermal insulation mortar and a preparation method thereof to solve the technical problems raised by the background technology.
[0007] The technical solution of the present invention is:
[0008] An inorganic mixed thermal insulation mortar comprises the following components by mass fraction:
[0009] Composite Portland cement: 21-25%;
[0010] Homemade machine-made sand: 15-35%;
[0011] Mineral stone powder: 6.5-10.5%;
[0012] Modified inorganic vitrified microspheres: 5-40%;
[0013] Active magnesium oxide: 0.01-5.0%;
[0014] Dispersible latex powder: 0.5-4%;
[0015] Cellulose ether: 0.011-0.015%;
[0016] Homemade crystalline waterproofing agent: 0.01-4%;
[0017] Polypropylene fiber: 0.05-0.15%.
[0018] The inorganic mixed thermal insulation mortar proposed by the present invention has the following beneficial effects:
[0019] Through the appropriate proportion of each component of the inorganic mixed insulation mortar, a high-quality, efficient and low-cost inorganic light aggregate mixed insulation material is obtained. The material is mainly mixed with ordinary silicate cement, refined sand, modified vitrified microspheres, active magnesium oxide, redispersible latex powder, cellulose ether, crystalline penetrating waterproofing agent and other raw materials. This material is designed for insulation and leveling of building floors. It is a composite mixed low-cost and efficient insulation material, which is expected to be industrialized, replace some of the existing complicated design insulation systems, improve the energy-saving efficiency and process technology level of building insulation, ensure project quality, reduce costs, and protect the ecological environment.
[0020] Preferably, the water-to-cement ratio of the inorganic mixed thermal insulation mortar is 1-1.5.
[0021] Preferably, the mass fraction of the dispersible latex powder is 0.5-1.5%, the mass fraction of the active magnesium oxide is 3-5.0%, and the mass fraction of the self-made machine-made sand is 18-22%.
[0022] Preferably, the mass fraction of the modified inorganic vitrified microspheres is 15-30%, and the mass fraction of the homemade crystalline waterproofing agent is 1.5-2.5%.
[0023] A method for preparing an inorganic mixed thermal insulation mortar comprises the following steps:
[0024] Weighing composite silicate cement, homemade machine-made sand, mineral stone powder, modified inorganic vitrified microspheres, active magnesium oxide, dispersible latex powder, cellulose ether, homemade crystalline waterproofing agent, and polypropylene fiber according to a preset ratio to obtain a weighed mixture;
[0025] Add the weighed mixture and an appropriate amount of mixing water into a mixer and stir until uniform to obtain a test mortar;
[0026] pouring the test mortar into a test mold of a preset size to form a plurality of test pieces;
[0027] Based on the size of the test piece, test and obtain test parameters of the test mortar, wherein the test parameters include shrinkage, compressive strength, dry density, thermal conductivity and porosity;
[0028] According to the test parameters, the proportions of the components of the mixture are adjusted to obtain an inorganic mixed thermal insulation mortar with performance that meets the requirements.
[0029] Preferably, the step of obtaining the shrinkage rate of the test mortar comprises:
[0030] Use a triple test die with holes at both ends and install a shrinkage probe;
[0031] Pour the test mortar into a test mold, and place it on a vibration table to vibrate for a first preset time to ensure that the test mortar evenly fills the test mold;
[0032] placing the formed test mold in a standard curing room for curing for a second preset time, removing the test mold after curing to obtain a sample, and recording the size of the sample;
[0033] Continue to cure the sample under standard test conditions for a third preset time to obtain a dried piece, and record the size of the dried piece;
[0034] The shrinkage rate of the test mortar is calculated by using a shrinkage rate calculation formula based on the size of the drying piece and the size of the sample.
[0035] Preferably, the shrinkage calculation formula includes:
[0036]
[0037] Among them, L 0is the measurement length of the second preset time, L is the test mold length, L d L is the sum of the lengths of the two probes embedded in the test block. t is the measurement length of the third preset time, and ω is the shrinkage rate.
[0038] Preferably, the step of obtaining the dry density of the test mortar comprises:
[0039] Placing the formed test piece in a drying oven for drying until the mass of the test piece is dried to a constant weight, and obtaining a plurality of test pieces with a constant weight;
[0040] The dry density of the test mortar is obtained by calculating the dry density using a dry density calculation formula based on the test piece of constant mass.
[0041] Preferably, the dry density calculation formula includes:
[0042]
[0043] Among them, ρ 0 is the dry density, m 0 is the mass after drying, and V is the volume of the specimen.
[0044] Preferably, the step of obtaining the thermal conductivity of the test mortar comprises:
[0045] The test piece is cured at room temperature for a fourth preset time, and the test piece after the fourth preset time is placed in a standard curing room for curing for a fifth preset time; the test piece after the fifth preset time is placed in a drying oven and dried to a constant weight, and the thermal conductivity coefficient of the test piece at a constant weight is measured using a measuring instrument. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0047] Figure 1 A line graph showing the effect of water-cement ratio on drying shrinkage of inorganic thermal insulation mortar is provided for the second embodiment of the present invention;
[0048] Figure 2 A line graph showing the effect of water-cement ratio on compressive strength and flexural strength of inorganic thermal insulation mortar is provided for the second embodiment of the present invention;
[0049] Figure 3 A line graph showing the effect of water-cement ratio on dry density of inorganic thermal insulation mortar is provided for the second embodiment of the present invention;
[0050] Figure 4 A line graph showing the effect of water-binder ratio on thermal conductivity of inorganic thermal insulation mortar is provided for the second embodiment of the present invention;
[0051] Figure 5 A line graph of water-cement ratio versus mass loss rate of inorganic thermal insulation mortar is provided for the third embodiment of the present invention.
[0052] The embodiments of the present invention will be further described below with reference to the accompanying drawings. DETAILED DESCRIPTION
[0053] In order to facilitate understanding of the present invention, the present invention will be described more fully below with reference to various embodiments, but the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thorough and comprehensive.
[0054] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0055] The embodiment of the present invention provides an inorganic mixed thermal insulation mortar, which includes the following components by mass fraction:
[0056] The following components are included by mass fraction:
[0057] Composite Portland cement: 21-25%;
[0058] Homemade machine-made sand: 15-35%;
[0059] Mineral stone powder: 6.5-10.5%;
[0060] Modified inorganic vitrified microspheres: 5-40%;
[0061] Active magnesium oxide: 0.01-5.0%;
[0062] Dispersible latex powder: 0.5-4%;
[0063] Cellulose ether: 0.011-0.015%;
[0064] Homemade crystalline waterproofing agent: 0.01-4%;
[0065] Polypropylene fiber: 0.05-0.15%.
[0066] The water-to-cement ratio of the inorganic mixed thermal insulation mortar is 1-1.5.
[0067] The mass fraction of the dispersible latex powder is 0.5-1.5%, the mass fraction of the active magnesium oxide is 3-5.0%, the mass fraction of the self-made machine-made sand is 18-22%, the mass fraction of the modified inorganic vitrified microspheres is 15-30%, and the mass fraction of the self-made crystalline waterproofing agent is 1.5-2.5%.
[0068] The embodiment of the present invention further provides a method for preparing an inorganic mixed thermal insulation mortar, comprising the following steps:
[0069] Weighing composite silicate cement, homemade machine-made sand, mineral stone powder, modified inorganic vitrified microspheres, active magnesium oxide, dispersible latex powder, cellulose ether, homemade crystalline waterproofing agent, and polypropylene fiber according to a preset ratio to obtain a weighed mixture;
[0070] Add the weighed mixture and an appropriate amount of mixing water into a mixer and stir until uniform to obtain a test mortar;
[0071] pouring the test mortar into a test mold of a preset size to form a plurality of test pieces;
[0072] Based on the size of the test piece, test and obtain test parameters of the test mortar, wherein the test parameters include shrinkage, compressive strength, dry density, thermal conductivity and porosity;
[0073] According to the test parameters, the proportions of the components of the mixture are adjusted to obtain an inorganic mixed thermal insulation mortar with performance that meets the requirements.
[0074] The method for preparing the above-mentioned inorganic mixed thermal insulation mortar, the step of obtaining the shrinkage rate of the test mortar comprises:
[0075] Use a triple test die with holes at both ends and install a shrinkage probe;
[0076] Pour the test mortar into a test mold, and place it on a vibration table to vibrate for a first preset time to ensure that the test mortar evenly fills the test mold;
[0077] placing the formed test mold in a standard curing room for curing for a second preset time, removing the test mold after curing to obtain a sample, and recording the size of the sample;
[0078] Continue to cure the sample under standard test conditions for a third preset time to obtain a dried piece, and record the size of the dried piece;
[0079] The shrinkage rate of the test mortar is calculated by using a shrinkage rate calculation formula based on the size of the drying piece and the size of the sample.
[0080] In the preparation method of the above-mentioned inorganic mixed thermal insulation mortar, the shrinkage rate calculation formula includes:
[0081]
[0082] Among them, L 0 is the measurement length of the second preset time, L is the test mold length, L d L is the sum of the lengths of the two probes embedded in the test block. t is the measurement length of the third preset time, and ω is the shrinkage rate.
[0083] The method for preparing the above-mentioned inorganic mixed thermal insulation mortar, the step of obtaining the dry density of the test mortar comprises:
[0084] Placing the formed test piece in a drying oven for drying until the mass of the test piece is dried to a constant weight, and obtaining a plurality of test pieces with a constant weight;
[0085] The dry density of the test mortar is obtained by calculating the dry density using a dry density calculation formula based on the test piece of constant mass.
[0086] The dry density calculation formula includes:
[0087]
[0088] Among them, ρ 0 is the dry density, m 0 is the mass after drying, and V is the volume of the specimen.
[0089] The method for preparing the inorganic mixed thermal insulation mortar comprises the following steps of obtaining the thermal conductivity of the test mortar:
[0090] Curing the specimen at room temperature for a fourth preset time, and placing the specimen after the fourth preset time in a standard curing room for curing for a fifth preset time;
[0091] The test piece after curing for the fifth preset time is placed in a drying oven and dried to a constant weight, and the thermal conductivity of the test piece at a constant weight is measured using a measuring instrument.
[0092] The following is a further description of the embodiments of the present invention in multiple embodiments. The embodiments of the present invention are not limited to the following specific embodiments. Within the scope of the unchanged main rights, appropriate changes can be made to the implementation.
[0093] Example 1
[0094] An inorganic mixed thermal insulation mortar comprises the following components by mass fraction:
[0095] Composite Portland cement: 21-25%;
[0096] Homemade machine-made sand: 20%;
[0097] Mineral stone powder: 6.5-10.5%;
[0098] Modified inorganic vitrified microspheres: 15-30%;
[0099] Active magnesium oxide: 4.0-4.5%;
[0100] Dispersible latex powder: 1%;
[0101] Cellulose ether: 0.011-0.015%;
[0102] Homemade crystalline waterproofing agent: 2%;
[0103] Polypropylene fiber: 0.05-0.15%.
[0104] The water-to-cement ratio of the inorganic mixed thermal insulation mortar is 1.2-1.3.
[0105] Among them, the specifications and models of each component are as shown in Table 1 below;
[0106] Serial number Test material name Specifications Suppliers 1 M32.5 composite silicate cement M3.25 House brand 2 Fly ash Level II Xinchangyuan 3 Machine-made sand 40-70 mesh self made 4 Inorganic vitrified microspheres 70-100 mesh Xinyang Mingda Non-metallic Mining 5 Modifier GX-792 Anhui Guibao Silicone New Materials 6 Magnesium Oxide Content ≥≥95% Weifang Haililong Magnesium Industry Co., Ltd. 7 Dispersible latex powder 5010 bonding type Wacker, Germany 8 Polypropylene (PP) fiber 9mm Wuhan Runxingyuan 9 Hydroxypropyl methyl cellulose 10W Tianpu Chemical 10 Bentonite Sodium type Dongshun Chemical 11 Homemade crystalline waterproofing agent Low alkali type self made
[0107] Table 1 Components and raw materials
[0108] The preparation method of the above-mentioned inorganic mixed thermal insulation mortar comprises the following steps:
[0109] (1) weighing composite silicate cement, homemade machine-made sand, mineral stone powder, modified inorganic vitrified microspheres, active magnesium oxide, dispersible latex powder, cellulose ether, homemade crystalline waterproofing agent, and polypropylene fiber according to a preset ratio to obtain a weighed mixture;
[0110] (2) adding the weighed mixture and an appropriate amount of mixing water into a mixer and stirring until uniform to obtain a test mortar;
[0111] (3) pouring the test mortar into a test mold of a preset size to form a plurality of test pieces;
[0112] (4) Based on the size of the test piece, test and obtain test parameters of the test mortar, wherein the test parameters include shrinkage rate, compressive strength, dry density, thermal conductivity and porosity;
[0113] (5) According to the test parameters, the proportions of the components of the mixture are adjusted to obtain an inorganic mixed thermal insulation mortar with performance that meets the requirements.
[0114] In this implementation, the test method of the test parameters is as follows;
[0115] Drying shrinkage test
[0116] Standard reference: JGJ / T "Standard for Test Methods for Basic Properties of Building Mortar".
[0117] Specimen molding: Three specimens of 40mm×40mm×160mm were made for each mix ratio.
[0118] Test mold preparation: Use a 40mm×40mm×160mm triple test mold with holes at both ends and install the shrinkage probe.
[0119] Mortar pouring: Pour the mixed mortar into the test mold and place it on a vibration table for 1 minute to ensure uniform filling.
[0120] Curing: After molding, place the specimen with the mold in a standard curing room for 7 days.
[0121] Initial measurement: Measure the length of the specimen immediately after demoulding and record it as the original length L 0 .
[0122] Continue curing: Continue curing under standard test conditions for up to 28 days.
[0123] Final measurement: Measure the length of the specimen after 28 days and record it as the length after drying L t .
[0124] Shrinkage calculation: Use the formula Where L 0 is the measurement length for 7 days, L is the test block length 160mm, L d L is the sum of the lengths of the two probes embedded in the test block. t The measurement length is 28 days.
[0125] ②Compressive strength and flexural strength test
[0126] Standard reference: "Test method for strength of cement mortar" (GB / T17671).
[0127] Specimen molding: Make prismatic specimens of 40mm×40mm×160mm.
[0128] Flexural test: First, perform a flexural test.
[0129] Compression test: The compressive strength test is carried out on the semi-prism specimens.
[0130] ③Dry density test
[0131] Standard reference: "Test methods for inorganic rigid thermal insulation products: density, moisture content and water absorption" (GB / T5486.2-2001).
[0132] Specimen molding: Make prismatic specimens of 40mm×40mm×160mm.
[0133] Drying: Place the specimen in a drying oven and dry it to constant weight.
[0134] Constant temperature maintenance: After 3 hours of constant temperature maintenance, ensure that the mass change rate between two measurements is less than 0.2%.
[0135] Dry density calculation: Use the formula Take the average value of 6 specimens, where m 0 is the mass after drying, and V is the volume of the specimen.
[0136] ④ Thermal conductivity test
[0137] Standard reference: "Determination of steady-state thermal resistance and related properties of insulation materials: Guarded hot plate method" (GB / T10294-2008).
[0138] Specimen preparation: Prepare specimens of 300mm×300mm×30mm.
[0139] Curing: Curing at room temperature for 3 days, then curing in a standard curing room for up to 28 days.
[0140] Drying: Place the sample in a drying oven and dry it to constant weight.
[0141] Measuring instrument: Use CD-DR3030 thermal conductivity measuring instrument.
[0142] ⑤Porosity test
[0143] Sample preparation: Take three bean-sized samples from the specimens cured for 28 days.
[0144] Test equipment: PoreMaster-60 fully automatic mercury intrusion instrument.
[0145] Testing process: Place the sample in a glass tube and then put it into a mercury intrusion instrument for porosity testing.
[0146] Example 2
[0147] This embodiment provides an inorganic mixed thermal insulation mortar, which includes the following components by mass fraction:
[0148] Composite Portland cement: 21-25%;
[0149] Homemade machine-made sand: 20%;
[0150] Mineral stone powder: 6.5-10.5%;
[0151] Modified inorganic vitrified microspheres: 15-30%;
[0152] Active magnesium oxide: 4.0-4.5%;
[0153] Dispersible latex powder: 1%;
[0154] Cellulose ether: 0.011-0.015%;
[0155] Homemade crystalline waterproofing agent: 2%;
[0156] Polypropylene fiber: 0.05-0.15%.
[0157] The water-to-cement ratio of the inorganic mixed thermal insulation mortar is 1.2-1.5.
[0158] The difference between this embodiment and embodiment 1 is that the water-binder ratio is 1.2, 1.3, 1.4 and 1.5 for the test. On the basis of the previous water-binder ratio of 1.0, the water-binder ratio is 1.2, 1.3, 1.4 and 1.5 for the test. The effect of the water-binder ratio on the drying shrinkage, compressive strength, flexural strength, dry density, thermal conductivity and porosity of inorganic active lightweight aggregate mixed thermal insulation mortar (inorganic mixed thermal insulation mortar) is investigated. The test results are as follows Figures 1 to 4 The influence of porosity is shown in Table 2.
[0159] Water-cement ratio 1.2 1.3 1.4 1.5 Porosity / % 34.12 35.73 37.90 42.31
[0160] Table 2 Effect of adhesive ratio on porosity of 28d inorganic mixed thermal insulation mortar
[0161] It can be seen that 1) with the increase of water-binder ratio, the drying shrinkage and internal porosity of inorganic active (light aggregate) mixed insulation mortar gradually increase and show an increasing trend, while the compressive strength, flexural strength, dry density and thermal conductivity of inorganic active (light aggregate) mixed insulation mortar all show a decreasing trend; and when the water-binder ratio is constant, its drying shrinkage growth rate is faster in the early stage and slower in the later stage. Compared with the inorganic active (light aggregate) mixed thermal insulation mortar with a water-binder ratio of 1.2, the compressive strength of the inorganic active (light aggregate) mixed thermal insulation mortar with a water-binder ratio of 1.3, 1.4 and 1.5 decreased by 13.1%, 40.0% and 73.8% respectively; the flexural strength decreased by 18.8%, 35.7% and 77.7% respectively; the dry density decreased by 8.3%, 19.4% and 33.3% respectively; and the thermal conductivity decreased by 4.6%, 11.3% and 21.4% respectively. The results show that the water-binder ratio has a great influence on the performance of the inorganic active (light aggregate) mixed thermal insulation mortar. Therefore, when preparing the inorganic microsphere thermal insulation mortar, the design performance indicators (design strength ≥3.5MPa, dry density ≤1000kg / m 3 , thermal conductivity ≤ 0.15 [W / (m·k)]), this project selects a water-cement ratio between 1.2-1.3, and optimizes the ratio of admixtures. The abbreviation of inorganic active (light aggregate) mixed thermal insulation mortar is inorganic mixed thermal insulation mortar.
[0162] Example 3
[0163] This embodiment provides an inorganic mixed thermal insulation mortar, which includes the following components by mass fraction:
[0164] Composite Portland cement: 21-25%;
[0165] Homemade machine-made sand: 20%;
[0166] Mineral stone powder: 6.5-10.5%;
[0167] Modified inorganic vitrified microspheres: 15-30%;
[0168] Active magnesium oxide: 4.0-4.5%;
[0169] Dispersible latex powder: 0.5-4%;
[0170] Cellulose ether: 0.011-0.015%;
[0171] Homemade crystalline waterproofing agent: 2%;
[0172] Polypropylene fiber: 0.05-0.15%.
[0173] The water-to-cement ratio of the inorganic mixed thermal insulation mortar is 1.2-1.3.
[0174] The difference between this embodiment and embodiment 1 is that: the dispersible latex powder content of cement is selected to be 0.5%, 1%, 2%, and 4% respectively for testing. The mass loss rate of the test blocks with different amounts of latex powder after 10, 20, 30, 40, and 50 dry-wet cycles is investigated; the strength of the test blocks before the dry-wet cycle and the compressive strength of the test blocks after 50 dry-wet cycles are compared, and the compressive strength reduction rate of the test blocks under each dispersible latex powder content and the influence of strength are calculated. The test results are shown as follows: Figure 5 And as shown in Table 3.
[0175]
[0176] Table 3 Compressive strength reduction rate
[0177] It is worth noting that the dry-wet cycle is one of the most severe environmental conditions that causes the performance degradation of building insulation materials. The dry-wet cycle environment will cause changes in the internal microstructure of the mortar, thereby causing changes in the mechanical properties of the mortar, greatly reducing its lifespan. In actual use, the vitrified microsphere insulation series mortar is often in an alternating dry-wet environment. Under the repeated action of dry-wet cycles for a long time, the mechanical stability and durability of the entire system will be affected. This application selects M32.5 cement (composite silicate cement) as the main cementitious material, and dispersed rubber powder can be used for synergistic effect. The change in its dosage has a great influence on the strength of the mortar.
[0178] Depend on Figure 5 It can be seen that within 20 dry-wet cycles, the mass loss rates of test blocks with different glue powder dosages are not much different, and the change trend is not obvious; after 30 dry-wet cycles, with the increase of glue powder dosage, the mass loss of thermal insulation mortar first decreases, and is the smallest when the dosage is 2%. When the dosage is 4%, the mass loss rate increases; after 40 and 50 dry-wet cycles, the overall trend is similar to that of 30 dry-wet cycles, the mass loss first decreases and then increases sharply, and this trend becomes more and more obvious.
[0179] It can be seen from Table 3 that before the dry-wet cycle, the compressive strength of the test block decreases sharply with the increase of the amount of rubber powder. When the amount is 4%, the strength drops sharply. After 50 dry-wet cycles, the compressive strength increases first and then decreases with the increase of the amount of dispersible latex powder, and the compressive strength decrease rate decreases first and then increases. Analyzing the reasons, the compressive strength of inorganic active (light aggregate) mixed insulation mortar is often closely related to the density of the internal structure of the test block. The redispersible latex powder forms a film on the solid surface to form a flexible connection, which can improve the tensile strength of cement stone to a certain extent. However, the addition of rubber powder will reduce the fluidity of the mortar, produce more large pores in the mixture, thereby reducing the density of the mortar, making it easier to produce through cracks under capillary pressure when it undergoes dry-wet cycles, causing local shedding. Therefore, before the dry-wet cycle, due to the bonding effect of the glue powder, the compressive strength of the thermal insulation mortar increases with the addition of glue powder, and only decreases when the dosage reaches 4%. However, after 50 dry-wet cycles, the decrease rate of the compressive strength of the thermal insulation mortar decreases when the dosage of the glue powder increases from 0.5% to 1%, but increasing the dosage of the glue powder from 1% increases the decrease rate of the compressive strength of the thermal insulation mortar. The reason is that when the dosage of the glue powder is low, the effect of the glue powder on improving the internal bonding force of the mortar plays a leading role, but after the dosage of the glue powder is increased to 1%, the effect of the glue powder on the density of the mortar gradually emerges, thereby increasing the compressive strength of the thermal insulation mortar. Therefore, after comprehensive consideration, the dispersible latex powder dosage of this project is 1% of the cement mass ratio for subsequent tests.
[0180] Example 4
[0181] This embodiment provides an inorganic mixed thermal insulation mortar, which includes the following components by mass fraction:
[0182] Composite Portland cement: 21-25%;
[0183] Homemade machine-made sand: 20%;
[0184] Mineral stone powder: 6.5-10.5%;
[0185] Modified inorganic vitrified microspheres: 15-30%;
[0186] Active magnesium oxide: 0-5%;
[0187] Dispersible latex powder: 1%;
[0188] Cellulose ether: 0.011-0.015%;
[0189] Homemade crystalline waterproofing agent: 2%;
[0190] Polypropylene fiber: 0.05-0.15%.
[0191] The water-to-cement ratio of the inorganic mixed thermal insulation mortar is 1.2-1.3.
[0192] The difference between this embodiment and embodiment 1 is that the dosage (W %) of active magnesium oxide is selected to be 0, 2.5, 3.0, 3.5, 4.0, 4.5, and 5.0 for testing.
[0193] It is worth noting that adding an appropriate amount of expansion agent has become an effective measure to improve the crack resistance and durability of mortar. Compared with traditional expansion agents, MgO expansion agent has the advantages of less hydration water requirement, stable hydration products and adjustable expansion performance, but its delayed expansion may bring about stability and expansion that is difficult to quantitatively predict. Therefore, this project first activates magnesium oxide. Based on the traditional citric acid method, a single factor test is conducted to study the effects of dosage, water pH, heating temperature, rotation speed, etc. on the activity of MgO, and add it to inorganic active (light aggregate) mixed insulation mortar to solve its crack resistance and durability problems, and explore the influence of its dosage change on mortar strength, construction and workability. The test results are shown in Table 4.
[0194] Serial number Active magnesium oxide content W% Shrinkage rate (%) 28d compressive strength (MPa) 1 0 0.4 2.8 2 2.5 0.25 3.0 3 3.0 0.23 3.3 4 3.5 0.21 3.3 5 4.0 0.20 3.4 6 4.5 0.14 3.9 7 5.0 0.13 4.0
[0195] Table 4 Effect of active magnesium oxide on the performance of inorganic active (light aggregate) mixed insulation mortar
[0196] It can be seen from Table 4 that with the continuous increase of the active magnesium oxide content W%, the corresponding 28d strength and shrinkage rate of the inorganic active (light aggregate) mixed insulation mortar also change accordingly. The larger the active magnesium oxide content, the lower the shrinkage rate and the higher the 28d compressive strength. When the content is between 4.0% and 4.5%, the 28d compressive strength is significantly improved. When the content is between 4.0% and 4.5%, the shrinkage rate is significantly improved. When it exceeds 4.5%, the test value tends to be stable. The reason for this is that active magnesium oxide is easy to form a binary cementitious system with cement, and the mineral composition of the hardened slurry is mainly Ca(OH)2, crystalline α-C 2 SH, unhydrated clinker minerals (C 3 S.C. 2 S), Mg(OH) 2 And a small amount of MgO. MgO hydrates in cement paste to generate Mg(OH) 2 , some Mg(OH) 2 They grow in situ and attach to the surface of the particles. Some migrate and grow on the surface of cement hydration products at a certain distance, and are enriched in the hydration product Ca(OH) 2 , around the CSH gel, and a small amount is dispersed in the tiny pores between the hydration products to fill the gaps. Therefore, the greater the amount of active magnesium oxide added, the greater the degree of hydration, the smaller the shrinkage rate, and the higher the strength.
[0197] Based on the analysis of the above test data, when the addition amount of active magnesium oxide is 4.0%, its shrinkage rate is 0.20%, and when the 28d compressive strength is 3.4, its detection performance meets all design requirements. Therefore, this project prefers to use an active magnesium oxide dosage of 4.0-4.5% for experimental research.
[0198] Example 5
[0199] This embodiment provides an inorganic mixed thermal insulation mortar, which includes the following components by mass fraction:
[0200] An inorganic mixed thermal insulation mortar comprises the following components by mass fraction:
[0201] Composite Portland cement: 21-25%;
[0202] Homemade machine-made sand: 15-35%;
[0203] Mineral stone powder: 6.5-10.5%;
[0204] Modified inorganic vitrified microspheres: 15-30%;
[0205] Active magnesium oxide: 4.0-4.5%;
[0206] Dispersible latex powder: 1%;
[0207] Cellulose ether: 0.011-0.015%;
[0208] Homemade crystalline waterproofing agent: 2%;
[0209] Polypropylene fiber: 0.05-0.15%.
[0210] The water-to-cement ratio of the inorganic mixed thermal insulation mortar is 1.2-1.3.
[0211] The difference between this embodiment and embodiment 1 is that the machine-made sand dosage (W%) is selected to be 15, 20, 25, 30, and 35 for testing.
[0212] It is worth noting that according to the actual situation of the insulation project, the stone powder content and gradation of the machine-made sand are adjusted under the premise of meeting the relevant national standards and engineering design requirements, so as to meet the various performance requirements of the insulation material. The machine-made sand is selected as the basic main material of the inorganic active (light aggregate) mixed insulation mortar, as the supporting material and main rigid aggregate of the main performance of the insulation mortar, and its dosage has a direct effect on the strength, apparent density, shrinkage rate and construction performance of the inorganic active (light aggregate) mixed insulation mortar. The test results are shown in Table 5.
[0213]
[0214] Table 5 Effect of machine-made sand aggregate on the performance of inorganic active (light aggregate) mixed insulation mortar
[0215] It can be seen from Table 5 that with the continuous increase of refined sand content W%, the apparent density and 28d strength of inorganic active (light aggregate) mixed insulation mortar are gradually increasing, while the shrinkage rate is gradually decreasing, and the mixing construction performance is gradually getting worse. When the mechanism exceeds 20%, the strength and shrinkage rate meet the design requirements, but the apparent density does not meet the requirements. The main reason for this is that its bulk density is the largest and the porosity is low. Therefore, after comprehensive analysis, an overall test study was conducted when the mechanism sand addition amount was 20%.
[0216] Example 6
[0217] This embodiment provides an inorganic mixed thermal insulation mortar, which includes the following components by mass fraction:
[0218] Composite Portland cement: 21-25%;
[0219] Homemade machine-made sand: 20%;
[0220] Mineral stone powder: 6.5-10.5%;
[0221] Modified inorganic vitrified microspheres: 5-30%;
[0222] Active magnesium oxide: 4.0-4.5%;
[0223] Dispersible latex powder: 1%;
[0224] Cellulose ether: 0.011-0.015%;
[0225] Homemade crystalline waterproofing agent: 2%;
[0226] Polypropylene fiber: 0.05-0.15%.
[0227] The water-to-cement ratio of the inorganic mixed thermal insulation mortar is 1.2-1.3.
[0228] The difference between this embodiment and embodiment 1 is that the dosage (W%) of the unmodified inorganic vitrified microspheres and the modified inorganic vitrified microspheres are 5, 10, 15, 20, 25, and 30 respectively for testing.
[0229] It is worth noting that the material is the key to inorganic thermal insulation materials and directly affects its thermal insulation efficiency. Therefore, this project selects vitrified microspheres as aggregates, which are an inorganic glassy mineral material. They are made by crushing volcanic rocks into ore sand and then expanding and sintering them in an electric furnace. The product is irregular spherical particles with a honeycomb cavity structure inside and a thin glass shell on the surface. It has the characteristics of light weight, high strength, and stable physical and chemical properties. However, if used directly, its water absorption rate is large, resulting in an increase in the water-binder ratio and a decrease in thermal insulation efficiency. Therefore, this project first studies the modification of vitrified microspheres, and then examines the modified vitrified microspheres as the main thermal insulation aggregate. Its admixture amount W% has a direct effect on the thermal conductivity and thermal insulation performance and apparent density of the thermal insulation mortar. The test results are shown in Table 6.
[0230]
[0231] Table 6 Effect of inorganic vitrified microspheres on the performance of inorganic active (light aggregate) mixed insulation mortar before and after modification
[0232] It can be seen from Table 6 that the dosage of vitrified microspheres directly affects the strength. The greater the dosage, the lower the strength. Comparing the dosage of modified vitrified microspheres, the greater the dosage, the faster the unmodified strength decreases. The effects of the vitrified microspheres before and after modification on the thermal conductivity and apparent density are compared. The thermal conductivity after modification is significantly lower than that before modification, and the apparent density does not change much. Therefore, according to the design requirements, the unmodified vitrified microspheres meet the design requirements at 15-20%, while the thermal conductivity value and apparent density of the modified vitrified microspheres meet the design requirements when the dosage is 15-30%. Based on the uncertain factors of the formula, it is convenient to adjust the formula. We choose the modified vitrified microspheres as the dosage. At the same time, the water absorption of the modified vitrified microspheres is low, and the effect on the water-cement ratio is small.
[0233] Example 7
[0234] This embodiment provides an inorganic mixed thermal insulation mortar, which includes the following components by mass fraction:
[0235] Composite Portland cement: 21-25%;
[0236] Homemade machine-made sand: 20%;
[0237] Mineral stone powder: 6.5-10.5%;
[0238] Modified inorganic vitrified microspheres: 15-30%;
[0239] Active magnesium oxide: 4.0-4.5%;
[0240] Dispersible latex powder: 1%;
[0241] Cellulose ether: 0.011-0.015%;
[0242] Homemade crystalline waterproofing agent: 0-4%;
[0243] Polypropylene fiber: 0.05-0.15%.
[0244] The water-to-cement ratio of the inorganic mixed thermal insulation mortar is 1.2-1.3.
[0245] The difference between this embodiment and embodiment 1 is that the dosage (W%) of the common waterproofing agent and the crystalline waterproofing agent are 5, 10, 15, 20, 25, and 30 respectively for testing.
[0246] It is worth noting that water absorption is a key factor affecting thermal conductivity. If the moisture content of the thermal insulation material increases, this will inevitably lead to an increase in the thermal conductivity of the material. Therefore, controlling water absorption is also one of the key technologies of this project. This project considers the durability of the waterproof and thermal insulation effects of the thermal insulation material, and develops a crystalline waterproofing agent suitable for inorganic thermal insulation materials. This material has the function of promoting the self-repair of cement-based materials, and the automatic healing of microcracks inside the vitrified microbead system has a permanent waterproofing effect. This project optimizes the combination of bentonite, fly ash and other components, strictly controls the content of calcium oxide, silicon dioxide, magnesium oxide, aluminum oxide and sulfur trioxide, and uses the hydroxide in the waterproofing agent to react with CO in the air. 2 The carbonates generated by the reaction and the unhydrated cement clinker continue to hydrate to generate certain crystals or amorphous products to repair the cracks of the insulation material and solve the problems of insulation and waterproof durability. Therefore, the effects of ordinary waterproofing agents and crystalline waterproofing agents on thermal conductivity and water absorption were investigated and compared, and the results are shown in Table 7.
[0247]
[0248] Through the experiment of adding different waterproofing agents in Table 7, it can be concluded intuitively that the water absorption rate of crystalline waterproofing agent is lower than that of ordinary waterproofing agent on the market, and the thermal conductivity coefficient does not change much. In order to improve the durability of thermal insulation and waterproofing, this project selects self-made crystalline waterproofing agent as an admixture, and its dosage is controlled at about 2%, which meets the design requirements.
[0249] From the above-mentioned Examples 1 to 7, the appropriate proportions of the components of the inorganic mixed thermal insulation mortar can be obtained, and then the inorganic active (light aggregate) mixed thermal insulation mortar material made by the process can be obtained. Its design goal and performance are to well integrate the performance characteristics of inorganic active (light aggregate) mixed thermal insulation mortar and cement mortar, taking into account the high strength, durability, and surface decoration functional characteristics of cement mortar, and the low thermal conductivity and thermal insulation performance characteristics of inorganic active (light aggregate) mixed thermal insulation mortar. The two are well integrated together to reduce the various drawbacks of layered and material-based construction, so that it has consistency in material performance, and the product meets the design requirements of Q / JXZK001-2021. It has the following technical indicators as shown in Table 8.
[0250] Project indicators Design performance values Measured value <![CDATA[Dry density / kg / m 3 > ≤1000 784 28d compressive strength / MPa ≥3.5 3.50 14d tensile bond strength / MPa ≥0.25 0.25 Shrinkage / % ≤0.20 0.19 1h consistency retention rate / % ≥60 65 Softening coefficient / % ≥0.6 0.77 Thermal conductivity, [W / (m·k)] ≤0.15 0.1070 Combustion performance A-level Level A1
[0251] The main technical indicators are shown in Table 8
[0252] The construction technical specifications of inorganic active (light aggregate) mixed thermal insulation mortar are as follows:
[0253] Construction preparation
[0254] Main equipment: Professional electricians are equipped with automatic mortar mixers and all circuits and water supply facilities.
[0255] Ensure the normal operation of the equipment, including wheelbarrow, wooden scraper, wooden trowel, iron trowel, splitter, watering can, shovel, wooden bucket of water, long-handled brush, broom, wire brush, chalk line bag, chisel and hammer.
[0256] Working conditions
[0257] 1. The cushion layer of the ground (or floor) and various pipelines pre-buried in the ground have been completed. The vertical pipes passing through the floor have been installed and the pipe holes have been tightly blocked. The rooms with floor drains should have flooding.
[0258] 2. The +50CM horizontal height line of the wall has been marked on the surrounding walls.
[0259] 3. The door frame has been erected and the inside of the frame has been protected to prevent damage from being caused by a trolley.
[0260] 4. The wall and ceiling plastering has been completed, and the roof waterproofing has been completed.
[0261] Operation process:
[0262] Base treatment - find elevation and draw lines - sprinkle water to moisten - apply plaster cakes and mark reinforcement - prepare and mix inorganic (light aggregate) mixed insulation mortar - brush floor interface treatment layer - lay inorganic (light aggregate) mixed mortar insulation layer - smooth with wooden trowel - press with iron trowel for the first time - press with the second time - press with the third time - maintain.
[0263] 1. Base treatment: first sweep away the dust on the base, brush it clean with a wire brush and chisel, remove the mortar skin and ash layer, brush off the oil stains on the base with a 10% caustic soda aqueous solution, and rinse the alkali solution with clean water in time.
[0264] 2. Find the elevation and draw the line: Based on the +50CM horizontal line on the wall, measure the surface elevation downwards and draw it on the wall.
[0265] 3. Sprinkle water to moisten: Use a watering can to evenly sprinkle water on the ground base.
[0266] 4. Plastering cakes and marking bars (or punching bars): Determine the thickness of the surface plastering (should not be less than 20MM) according to the surface elevation horizontal lines marked on the walls around the room, then draw a horizontal line to start plastering cakes (5CM*5CM), with a horizontal and vertical spacing of 1.5-2.00M. The plane on the plaster cake is the ground surface elevation. (If the room is large, in order to ensure the flatness of the overall surface, it is also necessary to apply marking bars (or punching bars), spread the insulation mortar between the plaster cakes, with the same width as the plaster cakes, and use a wooden trowel to pat it to be level with the upper surface of the plaster cakes. The mortar material mix ratio for plastering cakes and marking bars is the same as the mortar for ground insulation.)
[0267] 5. Mixing mortar: If the product used is the packaging specification, the packaging of this product can be unpacked. The amount of inorganic mixed thermal insulation mortar to be mixed at one time can be determined according to the mixing amount of the mortar mixing machine. First, add the mixing water for inorganic mixed thermal insulation mortar into the mixer with a mixing water-cement ratio of 1.1:1. Place this product in an inverted mixing container, start the mixing machine, and start stirring the floor insulation mortar. The stirring time should not be less than 3 minutes each time. After fully mixing, place the mixed mortar into the ash hopper truck and start using it. In order to fully mix and ensure the strength of the product in the later stage, the mixing water amount should be strictly controlled, and the construction consistency grade should not be greater than 50MM. If the product specification is bulk canning, water and electricity should be connected after the mortar tank is filled before construction. When the equipment is used for the first time, the construction should be started under the guidance of the manufacturer's professional and technical personnel. The water-cement ratio and consistency of the mortar mixing should be appropriately adjusted according to the needs of on-site construction. The mixed mortar should be transported to the construction area with a mortar dump truck. The principle of mixing the same amount as needed should be followed. Mortar that has been placed for a long time or has already initially set and solidified must not be used again in construction.
[0268] 6. Brush the interface bonding layer: Before laying the floor insulation mortar, the interface treatment layer should be brushed. (Before brushing, the remaining ash of the plaster cake should be cleaned up and then sprinkled with water to moisten it). Do not brush too large an area and lay the surface mortar as you brush.
[0269] 7. Laying floor insulation mortar: After applying the interface treatment layer, lay the floor insulation mortar. Spread the mortar evenly between the ash cakes (or between the marking bars), and then use a wooden scraper to scrape it flat according to the height of the ash cakes (or marking bars). If the ash cakes (or marking bars) have hardened during the mortar laying, knock off the used ash cakes (or marking bars) after scraping them flat with the wooden scraper, and fill them with mortar.
[0270] 8. Smooth it out: After the wooden scraper has scraped it out, immediately smooth it out with a wooden trowel, working from the inside out, and check the smoothness with a 2M ruler at any time.
[0271] 9. Press with iron trowel for the first time: After smoothing with wooden trowel, press with iron trowel for the first time immediately until slurry comes out. If the mortar is too thin and there is water seepage on the surface, you can evenly spread a mixture of dry cement and sand (1:1) (the sand must pass through a 3mm sieve), and then press with wooden trowel to make the dry mixture and mortar tightly combined. After absorbing water, press with iron trowel. If there is a grid requirement for the ground, draw grid lines on the surface layer, use a splitting trowel to open the seam, and then use a trowel to press the inside of the split seam until it is flat, straight and smooth. The above operations are all completed before the cement mortar begins to set.
[0272] 10. Second time of calendering: After the thermal insulation surface mortar has initially set, when people step on it and there are footprints but no sinking, use an iron trowel to calender it for the second time, filling the pits and concave areas while smearing and calendering, and it is required that there is no leakage, and the surface is flattened and calendered. After the gridded ground is calendered, use a trowel to calender it, so that the seam edges are straight, the gaps are clear, and the seams are smooth and straight.
[0273] 11. Third time of smoothing: The third time of smoothing is carried out before the final setting of the thermal insulation mortar (there will be slight footprints when people step on it but it will not sink). When there are no more smear marks left by the iron trowel, use the iron trowel to flatten, compact and smooth all the smear marks left by the second time of smoothing (it must be completed before the final setting).
[0274] 12. Maintenance: 24 hours after the ground is polished, cover it with sawdust or other materials and sprinkle water to keep it moist. The maintenance time should be no less than 7 days. People can go on the ground only when the compressive strength is reached.
[0275] 13. During winter construction, the indoor temperature must not be lower than +5℃.
[0276] 14. Apply skirting board: When the wall base is plastered according to the design drawing, the bottom mortar and surface mortar of the skirting board are applied twice. When the wall base is not plastered, the skirting board is only applied with the surface mortar. The specific construction process can refer to the operation process of applying cement mortar on the wall.
[0277] In summary, according to the inorganic mixed thermal insulation mortar and the preparation method thereof provided by the present invention, the key technology solved is;
[0278] (1) Modification technology of inorganic vitrified microsphere aggregate;
[0279] Thermal insulation is the core indicator of this project. If increasing strength on the basis of improving thermal insulation is the key technology of this project, it is essentially about how to reduce the thermal conductivity of the thermal insulation mortar, so as to achieve the overall thermal insulation performance technical design requirements of the material. This project mainly modifies the thermal insulation aggregate (inorganic expanded glass beads) through silane coupling agent. Through the encapsulation technology, a large number of hydroxyl groups are formed on the surface of the thermal insulation aggregate, which increases the affinity between the thermal insulation aggregates and makes it easier for the thermal insulation aggregates to combine with cement slurry to achieve the purpose of increasing strength.
[0280] (2) Balance the relationship between thermal conductivity of materials and the strength of thermal insulation mortar;
[0281] The addition of a large amount of lightweight aggregate modified inorganic glass microsphere aggregate particles will inevitably reduce the dry apparent density of the mortar. On the one hand, the thermal conductivity of the mixed mortar will decrease with the increase of its mixing amount, and the thermal performance will become better, but the strength will be greatly reduced. How to meet the thermal calculation and design requirements of the material while taking into account a certain strength cost of the ground leveling mortar project product is a key technical issue. The research starts from several aspects, optimizes and improves the rigid aggregate (mechanical sand) of the mixed material to achieve the best adaptation and filling effect. In addition, the lightweight aggregate is wrapped with hydroxyl groups to increase the affinity between the thermal insulation aggregates, and the thermal insulation aggregates are easier to combine with cement slurry to achieve the purpose of increasing the strength. The addition of a certain amount of redispersible latex powder has a membrane effect on the rigid structure of the mortar and improves the bonding strength of the internal structure of the mortar.
[0282] (3) This project adopts the encapsulation principle to carry out modification research on thermal insulation aggregates. Hydroxyl groups are grown on the surface of thermal insulation aggregates, which increases the affinity between aggregates, reduces shrinkage, solves the problem of material sinking and separation, and improves thermal insulation and strength.
[0283] (4) This project develops a new type of penetrating crystalline waterproofing agent, which has the advantages of being green, environmentally friendly and permanent waterproofing. It makes up for the shortcomings of many traditional waterproofing treatments and is applied to thermal insulation materials to solve the problem of thermal insulation durability of thermal insulation materials.
[0284] (6) This project takes into account the high strength and durability of cement mortar and the low thermal conductivity and thermal insulation of inorganic aggregate. The material properties are consistent and the combustion performance is Class A.
[0285] (7) This project aims to develop a high-quality, high-efficiency, low-cost inorganic lightweight aggregate mixed insulation material, which is mainly made of ordinary silicate cement, refined sand, modified vitrified microspheres, active magnesium oxide, redispersible latex powder, cellulose ether, crystalline penetrating waterproofing agent and other raw materials. This material is designed for insulation and leveling of building floors. It is a composite mixed low-cost and high-efficiency insulation material, which is expected to be industrialized and replace some of the existing complicated insulation systems, improve the energy-saving efficiency and process technology level of building insulation, ensure project quality, reduce costs, and protect the ecological environment.
[0286] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. An inorganic mixed thermal insulation mortar, characterized in that: The components include the following by mass fraction: Composite Portland cement: 21-25%; Homemade machine-made sand: 15-35%; Mineral stone powder: 6.5-10.5%; Modified inorganic vitrified microspheres: 5-40%; Active magnesium oxide: 0.01-5.0%; Dispersible latex powder: 0.5-4%; Cellulose ether: 0.011-0.015%; Homemade crystalline waterproofing agent: 0.01-4%; Polypropylene fiber: 0.05-0.15%.
2. The inorganic mixed thermal insulation mortar according to claim 1, characterized in that: The water-to-cement ratio of the inorganic mixed thermal insulation mortar is 1-1.
5.
3. The inorganic mixed thermal insulation mortar according to claim 1, characterized in that: The mass fraction of the dispersible latex powder is 0.5-1.5%, the mass fraction of the active magnesium oxide is 3-5.0%, and the mass fraction of the self-made machine-made sand is 18-22%.
4. The inorganic mixed thermal insulation mortar according to claim 1, characterized in that: The mass fraction of the modified inorganic vitrified microspheres is 15-30%, and the mass fraction of the self-made crystalline waterproofing agent is 1.5-2.5%.
5. The method for preparing the inorganic mixed thermal insulation mortar according to any one of claims 1 to 4, characterized in that: The following steps are involved: Weighing composite silicate cement, homemade machine-made sand, mineral stone powder, modified inorganic vitrified microspheres, active magnesium oxide, dispersible latex powder, cellulose ether, homemade crystalline waterproofing agent, and polypropylene fiber according to a preset ratio to obtain a weighed mixture; Add the weighed mixture and an appropriate amount of mixing water into a mixer and stir until uniform to obtain a test mortar; pouring the test mortar into a test mold of a preset size to form a plurality of test pieces; Based on the size of the test piece, test and obtain test parameters of the test mortar, wherein the test parameters include shrinkage, compressive strength, dry density, thermal conductivity and porosity; According to the test parameters, the proportions of the components of the mixture are adjusted to obtain an inorganic mixed thermal insulation mortar with performance that meets the requirements.
6. The method for preparing the inorganic mixed thermal insulation mortar according to claim 5, characterized in that: The step of obtaining the shrinkage rate of the test mortar comprises: Use a triple test die with holes at both ends and install a shrinkage probe; Pour the test mortar into a test mold, and place it on a vibration table to vibrate for a first preset time to ensure that the test mortar evenly fills the test mold; placing the formed test mold in a standard curing room for curing for a second preset time, removing the test mold after curing to obtain a sample, and recording the size of the sample; Continue to cure the sample under standard test conditions for a third preset time to obtain a dried piece, and record the size of the dried piece; The shrinkage rate of the test mortar is calculated by using a shrinkage rate calculation formula based on the size of the drying piece and the size of the sample.
7. The use of the inorganic mixed thermal insulation mortar according to claim 6, characterized in that: The shrinkage calculation formula includes: Wherein, L0 is the measurement length of the second preset time, L is the test mold length, and L d L is the sum of the lengths of the two probes embedded in the test block. t is the measurement length of the third preset time, and ω is the shrinkage rate.
8. The use of the inorganic mixed thermal insulation mortar according to claim 5, characterized in that: The steps of obtaining the dry density of the test mortar include: Placing the formed test piece in a drying oven for drying until the mass of the test piece is dried to a constant weight, and obtaining a plurality of test pieces with a constant weight; The dry density of the test mortar is obtained by calculating the dry density using a dry density calculation formula based on the test piece of constant mass.
9. The use of the inorganic mixed thermal insulation mortar according to claim 8, characterized in that: The dry density calculation formula includes: Among them, ρ0 is the dry density, m0 is the mass after drying, and V is the volume of the specimen.
10. The use of the inorganic mixed thermal insulation mortar according to claim 5, characterized in that: The steps of obtaining the thermal conductivity of the test mortar include: The test piece is cured at room temperature for a fourth preset time, and the test piece after the fourth preset time is placed in a standard curing room for curing for a fifth preset time; the test piece after the fifth preset time is placed in a drying oven and dried to a constant weight, and the thermal conductivity coefficient of the test piece at a constant weight is measured using a measuring instrument.